PENGARUH RENDAM KAKI AIR HANGAT TERHADAP PENURUNAN HIPERTENSI DAN PENINGKATAN KUALITAS TIDUR PADA WANITA MENOPAUSE DI DESA MUARA DILAM WILAYAH KERJA PUSKESMAS KUNTO DARUSSALAM II - Yuyun Bewelli Fahmi; Melda, Elvia; Nurkhasanah, Siti; Kristina, Evi; Janiarli, Masdi (Maternity and Neonatal : Jurnal Kebidanan, 2024)
Degenerative diseases appear more quickly when women have entered menopause. The symptoms that appear when women have entered menopause are known as menopausal syndromes. One of the symptoms of menopausal syndrome in women is hypertension and decreased sleep quality. Treatment of hypertension and sleep quality in menopausal women can be done pharmacologically and non-pharmacologically. One way of nonpharmacological treatment can be done by soaking in warm foot water. Menopausal women in village Muara Dilam the working area of the Kunto Darussalam II Health Center mostly do not know about appropriate non-pharmacological treatments for hypertension and sleep quality disorders apart from taking chemical drugs. The purpose of this study was to determine the effect of warm water foot soaks on reducing hypertension and improving sleep quality in postmenopausal women in village Muara Dilam the working area of the Kunto Darussalam II Health Center. This research method is quantitative analytic with a one group pre test and post test research design. Data collection used a questionnaire while data analysis used the t-dependent test. The sample in this study amounted to 35 respondents. Research results there is an effect of warm water foot soaks on reducing hypertension and improving sleep quality in menopausal women in the Muara village in the working area of the Kunto Darussalam II Public Health Center Rokan Hulu Regency with p-value = 0.000